2019
DOI: 10.5658/wood.2019.47.6.700
|View full text |Cite
|
Sign up to set email alerts
|

Determinate the Number of Growth Rings Using Resistograph with Tree-Ring Chronology to Investigate Ages of Big Old Trees

Abstract: To verify the possibility of using resistograph to estimate the age of big old living trees, we selected three Zelkova serrata and seven Pinus densiflora in Goesan. The mean diameters at breast height of Z. serrata and P. densiflora were 102 (92-116) cm and 80 (65-110) cm, respectively. The heights measured from the ground using a resistograph ranged at 1.2-4.3 m and 0.6-1.1 m for Z. serrata and P. Densiflora, respectively. The most appropriate needle speed to determine tree-ring boundaries for measuring ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The distribution of earlywood and latewood in tree rings was analyzed by the peaks and troughs of the waveform. The analog method that can quantify the measurement results ensures the feasibility of the micro-drilling resistance method for tree ring detection [48,49].…”
Section: Analog Micro-drilling Resistance Methodsmentioning
confidence: 99%
“…The distribution of earlywood and latewood in tree rings was analyzed by the peaks and troughs of the waveform. The analog method that can quantify the measurement results ensures the feasibility of the micro-drilling resistance method for tree ring detection [48,49].…”
Section: Analog Micro-drilling Resistance Methodsmentioning
confidence: 99%
“…The micro drill resistance instrument uses a motor to control the constant-speed penetration of the drill needle into wood. The drill resistance is positively correlated with wood density and the instruments can measure wood density indirectly [27][28][29][30][31][32][33]. The resistance drilling method has considerable advantages over other methods, including minimal tree damage, faster operation, and higher measurement sensitivity, making it a highly promising method for measuring wood density [22].…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of research has been done to explore the use of the micro drill resistance instrument for various application such as tree-ring analysis [2,[5][6][7], tree age [3,8], wood density measurement [9][10][11][12][13], tree decay detection [14]and structural timber condition assessment [15]. Rinn et al demonstrated that Resistograph profiles of coniferous and deciduous wood can reveal density variations inside tree rings caused by earlywood and latewood.…”
Section: Introductionmentioning
confidence: 99%